Keanekaragaman ikan lais (kryptopterus spp) berdasarkan karakter morfologi di danau teluk kota jambi - Subagyo, Agus (Biospecies, 2010)
Teluk Lake of Jambi have a potency to be developed for fishery. This research aims toinvestigate the diversity of lais fish (Kryptopterus spp.) based on their morphological characters.The research was carried out from Novemberto December 2008. The collected fish samples wereidentified their morphological characters in the Biological UP MIPA Laboratory at the University ofJambi. The results show that there are six species of fish Lais in the Teluk Lake includingKryptopterus limpok, K. crytopterus, K. schilbeidis, K. hexapterus, K. bicirrhis, and Hemisilurusmoolenburghi.